Mental Health, Smartphone Use Type, and Screen Time Among Adolescents in South Korea - Woo KS; Bong SH; Choi TY; Kim JW (Psychology Research and Behavior Management, 2021)
Kyung Soo Woo, Su Hyun Bong, Tae Young Choi, Jun Won Kim Department of Psychiatry, Daegu Catholic University School of Medicine, Daegu, Republic of KoreaCorrespondence: Jun Won KimDepartment of Psychiatry, Daegu Catholic University School of Medicine, 33 Duryugongwon-ro 17-gil, Nam-gu, Daegu, 42472, Republic of KoreaTel +82-53-650-4332Fax +82-53-623-1694Email f_affection@naver.comPurpose: The excessive use of smartphones for social interaction is associated with mental health. However, few studies have considered the purpose of smartphone usage and screen time together. Therefore, we investigated the impact of smartphone purpose and screen time on mental health using data from the 2017 Korea Youth Risk Behavior Web-based Survey (KYRBS).Participants and Methods: A total of 54,243 adolescents answered items on purpose and screen time of smartphone use, stress perception, sleep dissatisfaction, depressive symptoms, and suicide-related indicators. The purpose of smartphone usage was categorized as social interaction and non-social interaction, and the daily smartphone screen time was classified into three categories: < 2 hours, ≥ 2 hours but < 4 hours, ≥ 4 hours per day.Results: We determined that, on weekdays, stress perception, sleep satisfaction, depressive symptoms, and suicide-related indicators worsened in both groups that used smartphones for ≥ 4 hours per day. When using smartphone for ≥ 2 hours but < 4 hours per day on weekdays, depending on the smartphone use purpose, mental health outcomes differed between the two groups. On weekends, using smartphones for ≥ 2 hours but < 4 hours per day worsened sleep satisfaction but decreased suicide-related indicators in both groups. Mental health outcomes improved when participants used smartphones for ≥ 2 hours but < 4 hours per day but worsened when smartphones were used for ≥ 4 hours per day on weekends.Conclusion: Recommended screen time of smartphone is different depending on the purpose of smartphone use, and the risk of uncontrolled usage is emphasized, rather than the absolute screen time.Keywords: mental health, smartphone addiction, social interaction, social media